A neuroinformatics study to compare inhibition efficiency of three natural ligands (Fawcettimine, Cernuine and Lycodine) against Human Brain Acetylcholinesterase. (March 2015) - Shaikh, Sibhghatulla; Zainab, Tahreem; Shakil, Shazi; Rizvi, Syed Mohd. Danish
Abstract : Enzyme-inhibition is considered as a potent therapeutic approach to the treatment of diseases associated with acetylcholinesterase (AChE). The present study elucidates molecular interactions of human brain AChE, with three natural ligands Lycodine, Cernuine and Fawcettimine for comparison. Docking between these ligands and enzyme was performed using 'Autodock 4.2'. It was determined that polar and hydrophobic interactions play an important role in the correct positioning of Lycodine, Cernuine and Fawcettimine within the 'catalytic site' of AChE to permit docking. This approach would be helpful to understand the selectivity of the given drug molecule in the treatment of neurological disorder. Moreover, the present study confirms that Lycodine is a more efficient inhibitor of human brain AChE compared to Cernuine and Fawcettimine with reference to ΔG and Ki values.